Second Scholasticism and Black Slavery - Pich, Roberto Hofmeister (Veritas (Porto Alegre), 2019)
In order to systematically explore the normative treatment of Black slavery by Second Scholastic thinkers, usually placing the problem within the broad discussion of moral conscience and, more narrowly, the nature and justice of trade and contracts, I propose two stations of research that may be helpful for future studies, especially in what concerns the study of Scholastic ideas in colonial Latin America. Beginning with the analysis of just titles for slavery and slavery trade proposed by Luis de Molina S.J. (1535–1600), I show how his accounts were critically reviewed by Diego de Avendaño S.J. (1594–1688), revealing basic features of Second Scholastic normative thinking in Europe and the Americas. Normative knowledge provided by these two Scholastic intellectuals would be deeply tested throughout the last decades of the 17th century, especially by authors who sharpened the systemic analysis and a rigorist moral assessment of every title of slavery and slaveholding, as well as the requirements of an ethics of restitution. *** Segunda Escolástica e escravidão negra *** No intuito de explorar sistematicamente o tratamento normativo da escravidão negra por pensadores da Segunda Escolástica, que normalmente colocam o problema dentro da discussão ampla da consciência moral e, mais em específico, da natureza e da justiça do comércio e dos contratos, eu proponho duas estações de pesquisa que podem ser de ajuda para estudos futuros, em especial no que diz respeito ao estudo de ideias escolásticas na América Latina colonial. Começando com a análise dos títulos justos em favor da escravidão e do comércio de escravos propostos por Luis de Molina S. J. (1535–1600), eu procuro mostrar como os seus relatos foram recebidos criticamente por Diego de Avendaño S. J. (1594–1688), revelando traços básicos do pensamento normativo da Segunda Escolástica na Europa e nas Américas. O conhecimento normativo oportunizado por esses dois intelectuais escolásticos seria testado de forma profunda ao longo das últimas décadas do século 17, sobretudo por autores que aguçaram a análise sistêmica e a avaliação moral rigorista de todos os títulos de escravidão e de posse de escravos, bem como as exigências de uma ética da restituição. Palavras-chave: escravidão negra, Segunda Escolástica, justiça comutativa, probabilismo, Luis de Molina, Diego de Avendaño.